The work of the Reverend James Cameron of the Wesleyan Methodist Missionary Society from 1829 to 1835 - Van Heerden, Gary Paul (Rhodes University, Faculty of Divinity, Department of Divinity, 1993)
The name James Cameron is not a familiar one. Despite being one of the missionary pioneers of Methodism in southern Africa, serving for more than forty-six years in various districts and being elected as chairman of two of these districts, very few people have ever heard of James Cameron. Barnabas Shaw says of Cameron that he "excelled in preaching the great truths of the gospel, and applying them to the heart of sinners".¹ Whiteside describes Cameron as a "remarkable man ... well read in most things".² W.B. Boyce pays Cameron an even greater tribute: In my day, as a preacher and as a theologian, he was unequalled in South Africa; and I do not think that he was second in these respects to any of his brethren in England.³ Notwithstanding the high esteem in which he was held by prominent peers, Cameron is mentioned only in passing in a few secondary sources, and to date has not been the subject of academic research. The reason for this is not clear. He was well educated, read and wrote extensively, and most of his correspondence has been preserved. Cameron's Journal is very well written, containing some beautiful poetic sections. It is a personal record of a missionary coping with peculiar and difficult circumstances, and a record of how determination, courage and faith enabled Cameron to overcome seemingly insurmountable difficulties. Cameron's recording of his struggles help fill out our understanding of missionaries and their tasks and problems in the nineteenth century. I believe that so important a figure in South African Methodism should be examined and deserves a definitive study. The aim of this thesis has been to provide a reference to his work in the western Cape, possibly to form a basis for closer historical scrutiny. ¹ Shaw 1840:232 ² Whiteside 1906:374 ³ Boyce 1874:179-80.
Keywords: Cameron, James, 1800-1875; Wesleyan Methodist Missionary Society; Methodist Church of Southern Africa -- History